Single-cell RNA-Seq reveals the potential risk of anti-mesothelin CAR T Cell therapy toxicity to different organs in humans - Wen, Lu; Huang, Yu; Peng, Ling; Zhao, Kaiping; Sun, Yan; Lin, Zhicai; Chen, Yuanyuan; Li, Zhong; Qian, Qijun; Tong, Fan; Zhang, Ruiguang; Dong, Xiaorong (Frontiers in Immunology, 2022)
“On-target off-tumor” toxicity is a major challenge to the use of chimeric antigen receptor (CAR)-engineered T cells in the treatment of solid malignancies, because of the expression of target antigens in normal tissues. Mesothelin overexpression is associated with poor prognosis of multiple solid tumors, and would therefore appear to be a suitable antigen target. To understand the risk of toxicity to different organs on anti-mesothelin CAR T cell therapy, single-cell RNA sequencing (scRNA-seq) datasets derived from major human physiological systems were analyzed in this study, including the respiratory, cardiovascular, digestive, and urinary systems. According to scRNA-seq datasets, the organs were stratified into high or low risk based on the level of mesothelin expression. We report that the proportion of mesothelin-positive cells was 7.71%, 2.40% and 2.20% of myocardial cells, pulmonary cells and stomach cells, respectively, indicating that these organs could be at high risk of “on-target off-tumor” toxicity on anti-mesothelin CAR T cell therapy. By contrast, esophagus, ileum, liver kidney and bladder exhibited low mesothelin expression (<1%). Therefore, these organs could be regarded as at low risk. Thus, the risk of toxicity to different organs and tissues in anti-mesothelin CAR T cell therapy may be predicted by these scRNA-seq data.